Conformationally Constrained Sialyl Analogues as New Potential Binders of h‐CD22. (30th March 2022) - Forgione, Rosa Ester; Nieto, Ferran Fabregat; Di Carluccio, Cristina; Milanesi, Francesco; Fruscella, Martina; Papi, Francesco; Nativi, Cristina; Molinaro, Antonio; Palladino, Pasquale; Scarano, Simona; Minunni, Maria; Montefiori, Marco; et al.
Abstract: Here, two conformationally constrained sialyl analogues were synthesized and characterized in their interaction with the inhibitory Siglec, human CD22 (h‐CD22). An orthogonal approach, including biophysical assays (SPR and fluorescence), ligand‐based NMR techniques, and molecular modelling, was employed to disentangle the interaction mechanisms at a molecular level. The results showed that the Sialyl‐TnThr antigen analogue represents a promising scaffold for the design of novel h‐CD22 inhibitors. Our findings also suggest that the introduction of a biphenyl moiety at position 9 of the sialic acid hampers canonical accommodation of the ligand in the protein binding pocket, even though the affinity with respect to the natural ligand is increased. Our results address the search for novel modifications of the Neu5Ac‐α(2‐6)‐Gal epitope, outline new insights for the design and synthesis of high‐affinity h‐CD22 ligands, and offer novel prospects for therapeutic intervention to prevent autoimmune diseases and B‐cell malignancies. Abstract : The h‐CD22 ability to regulate the immune system has made this receptor an attractive therapeutic target. Here we report the characterization of the binding epitopes and affinities of two synthetic analogues bound to h‐CD22 together with the determination of tridimensional models of the protein‐ligand complexes.